Targeting the Nutritional Value of Proteins From Legumes By-Products Through Mild Extraction Technologies - Prandi, Barbara; Zurlini, Chiara; Maria, Cigognini Ilaria; Cutroneo, Sara; Di Massimo, Martina; Bondi, Marika; Brutti, Andrea; Sforza, Stefano; Tedeschi, Tullia (Frontiers in Nutrition, 2021)
Legumes have been known for centuries for their good nutritional properties. e. Unfortunately, during legume processing, from 5 to 25% of this production is wasted. However, these by-products can still be a rich source of useful compounds, such as proteins, which can still be used in food and feed formulations. The choice of the extraction technique is basic to preserve the nutritional value of proteins since drastic conditions of pH and/or temperature could damage them. In this work, two mild extraction techniques (direct assisted extraction – DAE, and enzymatic assisted extraction - EAE) were applied for protein extraction from legume by-products obtained from agro-industrial processes. The quality of proteins was evaluated considering protein integrity (SDS-PAGE, degree of hydrolysis, free amino acid content, racemization degree) and nutritional features (amino acid score, digestibility). DAE is the technique that has best preserved protein integrity, indicating the suitability of this technique for applications were the presence of whole proteins is important for the structure of the final product. The digestibility of proteins extracted with EAE is higher than that of proteins extracted with DAE, making this technique particularly suitable for those food and feed formulation were a high digestibility of proteins is required.